Santa Cruz, M. I., Marcos, G. E., Di Camillo, S. G. (compiladoras), Diálogo con los Griegos, Buenos Aires, Colihue Universidad, 2004, pp. 320 - Saldivia, Raquel Esther (2005)
Fil: Saldivia, Raquel Esther. UBA.